Pioneers in Unknown Territory: Teacher Perceptions and Use of Non-Conventional Instructional Tools - Nadelson, Louis S.; Juth, Stephanie M.; Hartman, Christina; Gedeborg, Sam; Glaze, Andrew (International Journal of Educational Technology and Learning, 2018)
In an ongoing effort to understand teacher adoption of innovative instructional practices and their consideration of non-conventional tools for teaching and learning we collected survey data from over 300 teachers. From the 44 teachers who participated in our research we found a lack of alignment between teacher personal use of technology for teaching, high levels of teacher-centered use of technology and low levels of student-centered access to technology for learning, and need for instructional technology professional development that is different than what the teachers are receiving. Our discussion includes possible explanations, implications, and directions for future research.